2006
DOI: 10.1016/j.exppara.2006.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania amazonensis: Biological and biochemical characterization of ecto-nucleoside triphosphate diphosphohydrolase activities

Abstract: The presence of Leishmania amazonensis ecto-nucleoside triphosphate triphosphohydrolase activities was demonstrated using antibodies against different NTPDase members by Western blotting, flow cytometry, and immunoelectron microscopy analysis. Living promastigote cells sequentially hydrolyzed the ATP molecule generating ADP, AMP, and adenosine, indicating that this surface enzyme may play a role in the salvage of purines from the extracellular medium. The L. amazonensis ecto-NTPDase activities were insensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
73
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 42 publications
10
73
1
1
Order By: Relevance
“…Analysis of nucleotide and adenosine concentrations was performed as previously described (Pinheiro et al 2006).…”
Section: Inoculation and Determination Of Infection Progres-mentioning
confidence: 99%
“…Analysis of nucleotide and adenosine concentrations was performed as previously described (Pinheiro et al 2006).…”
Section: Inoculation and Determination Of Infection Progres-mentioning
confidence: 99%
“…Of particular interest is extracellular ATP (eATP), which is expected to accumulate at the site of inflammation [12][13][14], important in immunity against microbial infection. The released enzymes include adenylate kinase, 5′-nucleotidase (and/or ATPase/phosphatase), ecto-ATPase [15], ecto-nucleoside triphosphate diphosphohydrolase (NTPDase) [16] and NdK. The last enzyme utilizes eATP as its principal substrate [9,10,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they showed higher expression and activity in amastigote than in promastigote forms and that adenosine down-regulated the expression of this enzyme. Additionally, they showed that adenosine and anti-E-NTPDase antibodies decreased the adhesion of promastigotes to mouse peritoneal macrophages [74] .…”
Section: Biochemical and Biological Roles Of Ecto-nucleotidases And Tmentioning
confidence: 99%
“…They showed for the first time that virulent L. amazonensis presented higher ecto-ATPase activity than the avirulent promastigotes. In 2006, Pinheiro and co-workers demonstrated that the surface E-NTPDase from L. amazonensis is a protein from the CD39 family and that this enzyme may play a role in the purine salvage pathway [74] . Summary overview of purinergic signaling in the context of the immune system during homeostasis, dangerous stimuli or in the face of Leishmania infection.…”
Section: Biochemical and Biological Roles Of Ecto-nucleotidases And Tmentioning
confidence: 99%
See 1 more Smart Citation